The 'Orsten'-More than a Cambrian Konservat-Lagerstätte yielding exceptional preservation - Maas, A; Braun, A; Dong, X; Donoghue, P; Müller, K; Olempska, E; Repetski, J; Siveter, D; Stein, M; Waloszek, D (2006)
In several areas of southern Sweden, limestone nodules, locally called Orsten occur within bituminous alum shales. These shales and nodules were deposited under dysoxic conditions at the bottom of what was most likely a shallow sea during the late Middle to Upper Cambrian (ca. 500 million years ago). Subsequently, the name 'Orsten' has been referred to particular, mainly arthropod, fossils from such nodules, and, in a wider sense, to the specific type of preservation of minute fossil through secondarily phosphatization. This preservation is exceptional in yielding uncompacted and diagenetically undeformed three-dimensional fossils. 'Orsten'-type preservation resulted from incrustation of a thin external layer and also by impregnation by calcium phosphate and, therefore, mineralization of the surface of the former animals during early diagenesis. Primarily, this type of preservation seems to have affected only cuticle-bearing metazoans such as cycloneuralian nemathelminths and arthropods. 'Orsten' preservation in this sense seems to be limited by size, in having yielded no partial or complete animals larger than 2 mm. On the other end of the scale, even larvae 100 μm long are preserved, often more complete than larger specimens, and details such as setules and pores smaller than 1 μm can be observed. Fossils preserved in such a manner are almost exclusively hollow carcasses, but can be filled secondarily; less common are completely phosphatized compact specimens. The high quality of preservation makes the Swedish 'Orsten' a typical Konservat-Lagerstätte. Yet, its special type of preservation is more widespread in time and geographical distribution than assumed initially, and the origin of the phosphate is not necessarily restricted just to one source. Subsequent to the first discoveries of limb fragments of Cambrian arthropods in 1975, animals in this special preservational type have been discovered in several continents and across a broad stratigraphic range including even Proterozoic strata. The latter have yielded early cleavage and metazoan embryonic stages, expanding knowledge on the preservational capacities of the 'Orsten'. Here, we report the recent status of our research on the 'Orsten' and give perspectives for future exploration on a worldwide scale, particularly in light of a recently formed international research group named Center of Orsten Research and Exploration (C.O.R.E.). © 2006.